2006
DOI: 10.1007/s10620-006-3121-3
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Effects of Dietary Resistant Starch and Fish Oil on Short-Chain Fatty Acid Production and Agonist-Induced Contractility in Ileum of Young Rats

Abstract: We have shown independently that dietary fiber and n-3 fatty acids can affect gut function. This study investigated the interactive effects of resistant starch (RS) (as high amylose maize starch [HAMS]) and tuna fish oil on ileal contractility. Four-week-old male Sprague Dawley rats were fed 4 diets that contained 100 g/kg fat as sunflower oil or tuna fish oil, with 10% fiber supplied as alpha -cellulose or HAMS for 6 weeks. Fish oil feeding led to higher ileal n-3 fatty acid levels (mainly as DHA) and higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 47 publications
2
12
0
Order By: Relevance
“…Although not determined in this study, we have shown previously that feeding small animal models with diets supplemented with fiber or RS as Hylon VII resulted in lower colonic pH and higher total SCFA levels as acetate, propionate, and butyrate [31,49,50]. Interestingly, when the diets were supplemented with RS and fish oil, the total SCFA levels were all higher except for butyrate [35].…”
Section: % Of Total Fa E P a D H A T O T E P A D H A T O T E P A D H mentioning
confidence: 49%
See 2 more Smart Citations
“…Although not determined in this study, we have shown previously that feeding small animal models with diets supplemented with fiber or RS as Hylon VII resulted in lower colonic pH and higher total SCFA levels as acetate, propionate, and butyrate [31,49,50]. Interestingly, when the diets were supplemented with RS and fish oil, the total SCFA levels were all higher except for butyrate [35].…”
Section: % Of Total Fa E P a D H A T O T E P A D H A T O T E P A D H mentioning
confidence: 49%
“…Frozen digesta (300 mg) from stomach, small intestine, cecum or colon or frozen tissue sections (150 mg) from the small intestine or colon were ground gently in a glass homogenizer and total lipids extracted in methanol/chloroform/water (2:4:1) (v:v:v) and separated by thin layer chromatography (TLC) and fatty acids methylated and analysed by gas liquid chromatography (GLC) as described previously [34,35]. Results are expressed as EPA, DHA, or total LC n-3 PUFA recovered as mg or as percentage of total fatty acid level or total phospholipid fatty acid level.…”
Section: Total Phospholipid Fatty Acid Analysis Of Gut Digesta and Timentioning
confidence: 99%
See 1 more Smart Citation
“…Feeding WKY rats 5% FO high in DHA for 4 wk resulted in 9.8% total n-3 PUFA (2% EPA, 1.4% DPA, and 6.3% DHA). We have also fed SD rats similar FO at 10% and achieved 11.9% total ileal n-3 PUFA (2.8% EPA, 1.4% DPA, 7.8% DHA) (8). These experiments suggested that tissue n-3 PUFA saturates of between 5 and 10% dietary FO contain high DHA.…”
Section: Figmentioning
confidence: 73%
“…Fish oil, butyrate, trans resveratrol and resistant starch are bioactive ingredients of interest as they all have a role in improving the health and well being of the population (Gil, 2002;Jang et al, 1997;Patten et al, 2006;Topping & Clifton, 2001). Particular focus of these benefits has been for the cardiovascular and gastrointestinal systems.…”
Section: Introductionmentioning
confidence: 99%